Rekonstruksi Pemikiran dan Posisi Sufi-Antisufi Ibn Taymīyah - Mukhammad Zamzami (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2017)
This article reanalyzes Ibn Taymīyah’s position and his thought on Sufism and anti-Sufism. The article is also expected to find the precise typology to describe Ibn Taymīyah’s Sufism qualification other than the Sunnī and Falsafī typologies. As a formalist and literalist thinker, Ibn Taymīyah has been famously known as an anti-Sufi Muslim scholar. There have been a number of modern Salafis who refute any relationship between Ibn Taymīyah and Sufism. Ibn Taymīyah has criticized such philosophical doctrines of Sufism as waḥdat al-wujūd, ḥulūl, and ittiḥād, which are considered to have deviated from the foundations of Islam. Along with his criticism, Ibn Taymīyah offers a solution by recovering the earliest and authentic traditions of Sufism when it is viewed as to have obscured the authenticity of knowledge based on the al-Qur’ān and Sunnah. Therefore, the product of his Sufism can be categorized in Salafi-Sufism typology in addition to other such popular typologies as Sunnī and Falsafī. The pattern of the Taṣawwuf Salafī—which is deemed as being appropriate to describe the existence of Ibn Taymīyah’s Sufism—does not, basically, accept ta’wīl upon the religious texts. His Sufism aims to strengthen one’s faith and help him/her purify their soul and morality.